Peran dan Tanggungjawab Orangtua terhadap Pendidikan Anak Perspektif Hadits Nabi Riwayat Abu Dawud - Thohirin, Thohirin; Muhid, Muhid; Nurita, Andris (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The remarkable progress of contemporary technology has a significant impact on the advancement and maturation of a child. It is important for a parent to guide their children to activities and positive behavior in accordance with the basis of Al – Qur’an, and hadits. This study employs an analytical-descriptive approach, which falls under the category of descriptive research. It involves analyzing and interpreting the historical account of Hadith No. 495 from Abu Dawud, attributed to the Prophet Muhammad SAW. The result of this study is that parents have a great responsibility in teaching and guiding their children to pray according to ages described in the hadits. in addition, it takes the rule of parents as strict guides in the matter of praying for children, even the parents feel the need to give a blow to the child’s rejection and defiance, the action is permissible. Of course, the punches given are educational punches, do not injure and do not have the potential to cause damage bones and teeth. Parents are also ordered to separate the beds for boys and girls when they are 10 years old.